(3GdRjGOI aj GdHfjI GdUQajI h OhQgG GdOdGdj (B: s (3ShQ GdMhGeje fehPLB (B/ s - (3YaGa GdYGHO eMeO Eebjbs; (3CMeO eMeO YHOGdOGje (B: s; (3LeGd CMeO YHOGdYRjR (B: s ((3GdbGgQI (B: s (3YaGa GdYGHO eMeO Eebjb (B: s, 2012)
(3JMOK GdHMK Zf GdacQ GdGKfi YTQj aj GdbQfjf GdJGSY h GdYGTQ GdgLQjjf h GdJWhQGJ GdJj dMbJ Hg (B: (3h CHQR GdeSJMOKGJ aj GdePgH f h GdJMhdGJ aj eSjQI GdJTjY (B: (3h GdYdeGA GdPjf cGf dge JCKjQ HGdZ aj gPjf GdbQfjf (B: (3h efgL YdeGA GdGKfi YTQjI aj OQGSI GdYbjOI ajgeG (B: (3h OhQ GdOhdI (B((3GdUahjI(B) (3aj fTQ GdJTjY GdGKfi YTQj (B: (3h GdUQGY GdSfj (B/ (3GdTjYj aj gPjf GdbQfjf s
(3GWQhMI (B((3eGLSJjQ(B) - (3LGeYI GdbGgQI (B- (3cdjI OGQ GdYdhe (B- (3bSe GdfMh h GdUQa h GdYQhVs
(3UOQ GjVG cbQU eOeLs
Keywords: (3GdHOGAs; (3GdUahjIs; (3GdacQ GdGKfi YTQjs